Tarekat Tījānīyah di Banjarmasin, Kalimantan Selatan: Perkembangan, Genealogi, dan Jaringan - Wardani; Saifuddin; Dzikri Nirwana (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2024)
The Tījānīyah is one of ṣūfī orders (tarekat, tharīqah) that developed in South Kalimantan, Indonesia. Even though its teachings has been ever considered controversial in Indonesia, it has arised, even developed in Banjarese society which was dominated by other sufi orders which generally had different doctrines from it, such as the Naqsyabandīyah and the Sammānīyah. In fact, network is one factor that plays an important role in that context. This article aims to explain why this sufi order, focusing on that is located in Banjarmasin, was able to develop in this region by tracing its historical development, teacher-student genealogy, and networks, both global, national and regional networks in South Kalimantan. This study is qualitative in nature and sourced from literature, both primary ones e.g. from documents and secondary ones taken from a number of books and articles. This article concludes that this sufi order has a genealogy that connects it to Sheikh Abū al-'Abbās Aḥmad ibn Muḥammad ibn al-Mukhtar who is known as Aḥmad al-Tijānī in the chain of his followers who connect with sheikhs in Indonesia. Genealogically, K.H. Ahmad Anshari, the founder of the sufi order in Banjarmasin, has a lineage from K.H. Badri Masduqi, then Sheikh Idrīs al-‘Irāqī, Sheikh Aḥmad Sukayrij al-Marākisyī, Sayyid al-Syarīf Aḥmad al-Badawali, Sheikh Ali al-Tamasini, ending with Sheikh Aḥmad al-Tījānī. Thus, its lineage comes from the East Java network. Its development on the island of Java itself began with the role of Sheikh ‘Alī ibn Abdullāh al-THayyib at the beginning of the 20th century AD (between 1918 and 1922 AD). Its development in East Java was due to the important role of K.H. Idris Masduqi who has a genealogical relationship, not only with sheikhs on the island of Java, but also with the Moroccan network, where it first spread, namely through Sheikh Idrīs al-Marzūqī.